2003
DOI: 10.1017/s0266467403003055
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall but not selective logging affect changes in abundance of a tropical forest butterfly in Sabah, Borneo

Abstract: eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
5
28
1
1
Order By: Relevance
“…This is in agreement with a study by Hill et al [22] on tropical butterfly communities which found that these were diverse communities with many endemic species dependent on closed-canopy forests. This is because closed-canopy forests create microhabitats which are suitable for the butterflies.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with a study by Hill et al [22] on tropical butterfly communities which found that these were diverse communities with many endemic species dependent on closed-canopy forests. This is because closed-canopy forests create microhabitats which are suitable for the butterflies.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, tropical butterflies have been shown to be sensitive to seasonal changes in rainfall (Barby 1995;Hill et al 2003). Wynter-Blyth (1957) documented 835 species from the eastern Himalaya in sharp contrast to only 415 species from the western Himalaya.…”
Section: Introductionmentioning
confidence: 99%
“…Cerrado, could explain a large portion of the temporal variation in Satyrinae abundance (Braby 1995;Hill et al 2003;Ribeiro & Freitas 2011).…”
Section: Figmentioning
confidence: 99%